Transcriptomics profiling of Niemann-Pick type C patients: activation of the unfold protein response in a specific case - Encarnação, Marisa (2020)
Background: Niemann-Pick type C (NP-C) is a neurodegenerative Lysosomal Storage Disease (LSD) with a heterogeneous clinical presentation secondary to abnormal intracellular accumulation of cholesterol. We have studied a patient with clinical diagnosis of NP-C but presenting inconclusive results regarding biomarkers testing and molecular analysis. To better characterize this patient, we have performed NGS-based technologies (targeted DNA sequencing and single cell-RNA sequencing). Methods: For the molecular diagnosis we used a NGS gene panel followed by the analysis of cDNA (in the patient and both parents). Latter, we have used massively parallel single cell RNA-seq (MARS-Seq) to address gene profiling changes and better characterize the pathomechanisms related to specific disease-causing mutations in this patient as well as in two NPC patients. The most prominent hits from this transcriptomics analysis were validated by qRT-PCR. Results and Discussion: Using our targeted NGS panel we identified two novel mutations in NPC1 gene (p.V505G; p.V562V). Next, through cDNA analysis of one of the patient parents we were able to understand the impact of the V562V silent mutation located in the middle of the exon 11. This mutation leads to exon 11 skipping giving origin to an out-of-frame transcript and eliciting the nonsense-mediated decay pathway. This mechanism contributed to the almost absence of the mutant transcript in the patient. Thus, we were not able to easily detect it in the sequencing electropherogram of the patient which turned the molecular diagnosis more challenging. By its turns, apparently the presence of the other mutation (the missense V505G) impairs the proper NPC protein folding leading to its ER retention. In fact, the MARS-Seq analysis of this patient showed that a number of genes were upregulated and a significant number of the highly enriched genes are related to the unfold protein response (UPR).